The Impact of Income Diversification on the Performance of South Korea’s Commercial Bank - Muhammad Faruq Abdulhakim; Vera Intanie Dewi; Maria Widyarini (Accounting and Finance Studies, 2024)
Research Aims: The aim of this research is to investigate the impact of income diversification on the performance of 12 commercial bank in South Korea. Design/methodology/approach: Modern portfolio theory (MPT) is applied as theoretical framework. Panel data regression is used to reach the aim by collecting the yearly data started in 2015-2022 from BoK and South Korea’s FSS. Research Findings: The outcome found the income diversification is negative and significant impact on the bank performance. It also found out that internationalized bank has a better performance than the bank that operates domestically. Last, the control variable (bank size and South Korea’s macroeconomic condition) has positive impact on the bank performance. Theoretical Contribution/Originality: To show the research freshness, this research added internationalization as dummy variable to seize the difference on the performance between the bank that has additional income diversification strategy and the bank that just operates domestically.